THE EFFECT OF ORGANIZATIONAL JUSTICE ON EMPLOYEE PERFORMANCE WITH WORK ETHIC AS AN INTERVENING VARIABLE - Hardianto, Hardianto; Nursaid; Martini G, Ni Nyoman Putu (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The aim of this research is to analyze the influence of organizational justice on work ethic, analyze the influence of organizational justice on employee performance, analyze the influence of work ethic on employee performance, and analyze the influence of organizational justice on employee performance through work ethic as an intervention. Method: This research design uses mixed methods, namely a combination of qualitative and quantitative methods. The population in this study were honorary employees who worked at the Jember Regency Transportation Service, totaling 200 people and the sample size determined referring to the Slovin Formula was 133 respondents. Data processing in this research uses Variance-based SEM or Partial Least Square (SEM-PLS) with the Warp-PLS 7.0 SEM PLS program. Results: Research findings state that there is a positive and significant influence of organizational justice on work ethic. There is a positive but not significant influence of organizational justice on employee performance. There is a positive and significant influence of work ethic on employee performance. There is a positive and significant influence of organizational justice on employee performance through work ethic as an intervening variable. Novelty: This research uses a model of factors that influence employee performance by involving organizational justice and work ethic (as an intervening).